2007
DOI: 10.1186/1471-244x-7-11
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh Postnatal Depression Scale (EPDS): translation and validation study of the Iranian version

Abstract: Background: The Edinburgh Postnatal Depression Scale (EPDS) is a widely used instrument to measure postnatal depression. This study aimed to translate and to test the reliability and validity of the EPDS in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(176 citation statements)
references
References 27 publications
8
159
1
6
Order By: Relevance
“…Most studies (31/41, 76%) investigated risk and protective factors, while the remainder 11,12,29,33,35,41,42,44,54,56 only reported prevalence data. Potential risk factors for CPMDs in women in lowand middle-income countries reflected diverse conceptual frameworks and differed between studies.…”
Section: Socioeconomic and Intermediary Determinantsmentioning
confidence: 99%
“…Most studies (31/41, 76%) investigated risk and protective factors, while the remainder 11,12,29,33,35,41,42,44,54,56 only reported prevalence data. Potential risk factors for CPMDs in women in lowand middle-income countries reflected diverse conceptual frameworks and differed between studies.…”
Section: Socioeconomic and Intermediary Determinantsmentioning
confidence: 99%
“…The HADS has been translated into Persian (Farsi), and its psychometric properties have been established in Iranian populations. 12 …”
Section: Hospital Anxiety and Depression Scale (Hads)mentioning
confidence: 99%
“…14 In fact, we have previously found that EPDS could have two dimensions (anxiety and depression), 9 whereas others have even found three-dimensional factor structures (depression, anxiety and suicide 6,15 or depression, anxiety and anhedonia). 16 Furthermore, some studies have shown that other shorter EPDS versions, including a 7-item version and even a 2-item version, are also highly accurate for assessment of depression.…”
Section: Discussionmentioning
confidence: 99%